Support Vector Regression–Based Model for Multizone Electricity Consumption Forecasting - Nabila Farida; Indrianto (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2025)
This study aims to develop and evaluate a multi-zone short-term electricity consumption prediction model based on weather factors using the Support Vector Regression (SVR) method to support more efficient and adaptive power system planning in response to climate variability. Ten-minute resolution electricity consumption data from three zones was combined with variables of air temperature, relative humidity, wind speed, and solar radiation. The research process included data preprocessing, temporal feature engineering, time-based data partitioning, and SVR hyperparameter optimization with RBF kernel. Model performance was evaluated using Root Mean Square Error (RMSE), Mean Absolute Error (MAE), and coefficient of determination (R²) metrics, and compared with reference models such as linear regression, Random Forest Regression, and Artificial Neural Network. The results of the experiment show that SVR provides the best accuracy at high temporal resolution. At 10-minute aggregation, the MAPE values obtained were 4.78% (Zone 1), 4.11% (Zone 2), and 9.25% (Zone 3). Model performance declines as the level of time aggregation increases, indicating that the effectiveness of SVR is influenced by the temporal scale and load characteristics of each zone. These findings show that SVR works effectively for weather-based electricity load forecasting in various zones at high temporal resolution, although its performance declines at larger aggregation scales. Keywords: Multizone electric power consumption; Short-term load forecasting; Weather/meteorological factors; Support Vector Regression (SVR); Intelligent energy management systems.